2006
DOI: 10.1038/sj.bmt.1705416
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of FDG-PET scan imaging in lymphoma patients undergoing autologous stem cell transplantation

Abstract: We conducted a retrospective analysis of 50 lymphoma patients (Hodgkin's disease and non-Hodgkin's lymphoma) who had an 18 F-fluoro-deoxyglucose positron emission tomography (FDG-PET) scan after at least two cycles of salvage chemotherapy and before autologous stem cell transplantation (ASCT) at our institution. The patients were categorized into FDG-PET negative (N ¼ 32) and positive (N ¼ 18) groups. The median follow-up after ASCT was 19 months (range: 3-59). In the FDG-PET-negative group, the median progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 24 publications
7
59
0
1
Order By: Relevance
“…In addition, our data confirmed that PET status is correlated strongly with patient prognosis. Recently, as reported by Svoboda et al, 33 it was observed that a positive PET result before ASCT indicated a poor chance of achieving a durable response. In other words, an accurate evaluation of the response to salvage chemotherapy is highly predictive of outcome after ASCT.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, our data confirmed that PET status is correlated strongly with patient prognosis. Recently, as reported by Svoboda et al, 33 it was observed that a positive PET result before ASCT indicated a poor chance of achieving a durable response. In other words, an accurate evaluation of the response to salvage chemotherapy is highly predictive of outcome after ASCT.…”
Section: Discussionmentioning
confidence: 77%
“…More recently, some studies indicated that 18 FDG-FDG-PET also provides useful information about disease status before ASCT and even allogeneic stem cell transplantation in relapsed or refractory HL and non-Hodgkin's lymphoma, with a significant correlation between pretransplant PET status and prognosis [20][21][22][23][24][25][26]. CT scan is the most used in restaging lymphoma; however, some authors reported that history and physical examination could be the standard approach to follow-up because in most cases early recurrence is first suspected by the patient himself or by the physician, even with routine screening including CT scans [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective review by Svoboda et al 12 , the charts of 50 patients were analyzed who had undergone FDG PET scanning after at least two cycles of salvage chemotherapy, but prior to ASCT. Of the 50 patients, 31 had NHL, including aggressive and indolent subtypes, and 19 patients had HD.…”
Section: Referencesmentioning
confidence: 99%